bauHOF NGS: A design-build laboratory for sustainable constructions and collective actions - Simon-Meyer, Tim; Leon Elbern, Luise; Tischler, Julius; Schröter, Sebastian (EAAE Annual Conference Proceedings, 2025)
In response to the pressing demand for sustainable spatial practices and for systematic change, we propose an experimental effort that challenges traditional approaches in architectural education and research, fostering sustainability, inclusivity and collaborative decision-making. Situated in the rural area of Niedergrunstedt, our project “bauhHof NGS’’ revitalizes a historic farm, transforming it into a design-build laboratory for minimal and mobile constructions and multidisciplinary exchange. Emphasizing transparent negotiation and the importance of local resources, including material, physical and social knowledge, "bauhHof NGS" seeks to establish a platform that encourages interaction among students, the local community, and various urban and rural realities. Through a series of workshops, expert inputs and community events, we test diverse and interdisciplinary approaches and methods for co-creation. The students learn how to approach, communicate and deal with different needs and ideas within their group and how to integrate and negotiate different visions by partnering with various stakeholders, including neighbors, technical experts and policymakers.